A natureza do urbano - Francisco Capuano Scarlato; Everaldo Batista da Costa (Confins)
Perception, essence and existence are potential phenomenological categories in the understanding of the nature of urban in history. Seeking to contribute with the theorical debate of the essence and the nature of the urban, this article proposes, methodologically, three structured points: i) recognizes the importance of the existentialist phenomenology and of the historical materialism in the the interpretation of that nature; ii) discusses the nature of urban by the objectivity and subjectivity that involve cities in history; iii) consideres the historical center of cities as memory in the urban totality and dialectical synthesis in the nature of urban. Therefore, the urban society is regarded as a spatial condition generated from the historical and existential construct and inhabit, on behalf of domination and freedom, that preceed modern industrialization.